The identification and characterization of the p.G91 deletion in CRYBA1 in a Chinese family with congenital cataracts - Dan Li; Qinghe Jing; Yongxiang Jiang (BMC, 2019)
Abstract Background Mutations in more than 52 genes have been identified in isolated congenital cataracts, the majority of which are located in crystalline and connexin (gap junction) genes. An in-frame one amino acid deletion in the beta-crystalline gene CRYBA1 has been reported in several different Chinese, Caucasian and Iranian families of congenital cataracts. Further functional studies are needed to confirm the variant pathogenicity. Methods The purpose of this study is to identify the genetic causes that contribute to congenital cataracts with esotropia and nystagmus in a Chinese family. Whole-exome sequencing was performed on samples from all five family members. The two brothers of the father and their daughters were then enrolled in the study, and 40 suspected variants were sequenced among the 9 subjects using Sanger sequencing. The mRNA and protein levels of CRYBA1 in the lens epithelium from cataract patients and normal controls were compared using quantitative polymerase chain reaction (qPCR) and Western blot analyses. The wild-type and mutated forms (p.G91del) of CRYBA1 cDNA were transfected into two types of cell lines, and the expression level of exogenous CRYBA1 was measured by Western blot analysis. The exogenous CRYBA1 proteins were visualized by immunofluorescence staining. Results In this two-generation family, all three descendants inherited congenital cataracts with esotropia and nystagmus from the father, while the mother's lens was normal. After two rounds of sequencing, CRYBA1 (c. 269-271 del, p.G91del) was identified as the mutation responsible for the autosomal dominant congenital cataract in the Chinese family. CRYBA1 showed lower expression in cataract lenses than in control lenses. The deleted form (p.G91del) of CRYBA1 showed lower expression and was more aggregate to the cell membrane than the wild-type CRYBA1. Conclusions We performed molecular experiments to confirm that the p.G91del mutation in CRYBA1 results in abnormal expression and distribution of CRYBA1 protein, and this study could serve as an example of the pathogenicity of an in-frame small deletion in an inherited eye disorder.